Clinical and laboratory profile of tuberculosis in HIV positive individuals - B., Sandhya Rani; Bhandarkar, Varsha R.; Nandalike, Prathvi; Reddy, Machandra (International Journal of Research in Medical Sciences, 2022)
Background: Tuberculosis (TB), major public health problem in most of the developing countries. There is significant difference in the laboratory profile of tuberculosis in human immuno-deficiency virus (HIV) infected compared to immunocompetent host. Prompt diagnosis and treatment of tuberculosis in HIV infected will improve the morbidity and mortality associated with dual infection. Objectives of the research were: to study about the clinical profile of tuberculosis in HIV positive individuals; and also, to study about the laboratory profile of tuberculosis in HIV positive individuals. Methods: Patients with HIV positive status who fulfill the inclusion and exclusion criteria and admitted in Adichunchanagiri hospital and research center, BG Nagara Mandya district, Karnataka India, during the period of January 2020 to June 2021. Results: Fever was the most common symptom (92.8%). Most common manifestation was extrapulmonary TB (54%). TB meningitis was the most common extra pulmonary involvement seen in 28.67%. Amongst patients with pulmonary TB, 6.3% of cases were smear positive for AFB bacilli, 58% of cases had pulmonary infiltrates on chest X-ray. In all cases of extra pulmonary TB (EPTB) CD4T cell counts were <200 cells/μl. Conclusions: Chest X-rays were atypical with more of lowerzone infiltrative lesions. Sputum acid-fast bacillus (AFB) is negative in most of the patients with pulmonary TB, however had sputum cartridge based nucleic acid amplification test (CBNAAT) positive status, hence sputum CBNAAT remains the gold standard investigation. Fluid analysis with ADA correlation holds good for the diagnosis of TB meningitis and tubercular pleural effusion.